¿Racial Discrimination in Inclusive Education? A perspective from critical interculturality - Delbury, Perrine (2020)
The overrepresentation of ethnic minorities’ students as students with special education needs is a well-investigated international phenomenon. This paper is an essay aiming to contribute to the discussion, from the perspective of critical interculturality, to unveil how the phenomenon is embedded into the colonial matrix of power. At first, it presents the theoretical framework of critical interculturality and contextualizes the problem. The second part develops three arguments through a discussion about the respective roles of social rules, public educational policies, and inclusive pedagogy in contributing to this phenomenon. It concludes that, at the foundation of the inclusive education discourse, lays racial discrimination which imposes a monocultural definition of disability and normality to ethnic cultures.